The effect of slope steepness on soil erosion - Ali, Mohd Fozi; Said, Salim (1999)
The degree and length of the slope are two essential features of topography in relation to runoff and soil erosion. Dunne (1977) observed that topographic steepness is a significant factor effecting sediment yields. Soil losses can be expected to increase with slope length and steepness as a result of respective increases in volume and velocities of surface runoff. Steep slopes are often susceptible to landslides even under forest conditions and such slope become more susceptible to erosion once disturbed. The observations of this study will be made using the Soil Erosin Gauge (Baharuddin, 1995) on three categories of slopes; gentle, moderate, and steep slopes. Previous studies had concluded that the relation between slope steepness and soil loss was curvilinear. Investigation by Zingg (1940) showed that the relationship between steepness of slope and soil erosion could be represented by the power equation y = axb where b is 1.49, a is 0.065, x is the percent of slope steepness and y is the coded weight of soil loss. The USLE slope steepness factor was developed (Wischmeier and Smith, 1978) by the equation S = 65.41sin20 + 4.56sin0 + 0.065 where 0 is the angle of slope steepness in degrees. The percent slope factor is also known to interest with management practices such as contouring and terracing.